Replacement of Congenitally Missing Maxillary Lateral Incisor with Two-Buccal-Retainer Resin-Bonded Fixed Dental Prosthesis Modified by Proximal Boxes - Lama Marmar; Safaa Bassam Shihabi; Issam Jamous (Hindawi Limited, 2022)
A 21-year-old male patient with congenitally missing maxillary right lateral incisor presented to Fixed Prosthodontics Department at the Faculty of Dentistry, Damascus University (Damascus, Syria). A two-buccal-retainer lithium disilicate glass-ceramic resin-bonded fixed dental prosthesis (RBFDP) was chosen to replace the missing tooth. This clinical report describes a novel preparation design of two-buccal-retainer lithium disilicate glass-ceramic RBFDP modified by proximal boxes. A recall appointment after 3 years showed no fracture, no de-bonding, no secondary caries, and no staining in prosthesis margins. Color matching with natural teeth was excellent, and the patient was satisfied.